2006
DOI: 10.1063/1.2192755
|View full text |Cite
|
Sign up to set email alerts
|

Zonal flows generated by small-scale drift-Alfvén modes

Abstract: The generation of zonal flows by small-scale drift-Alfvén (SSDA) modes is investigated. It is shown that these zonal flows can be generated by a monochromatic wave packet of SSDA modes propagating in the ion diamagnetic drift direction. The corresponding zonal-flow instability resembles a hydrodynamic one. Its growth rate depends on the spectrum purity of the wave packet; it decreases for relatively weak spectrum broadening and the instability turns into a resonant one, and eventually is suppressed, as the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 24 publications
(33 reference statements)
0
51
1
Order By: Relevance
“…13 is connected only with the spectral analysis of investigation and we retain the main approach to the solving of the problem and all initial equations as in Ref. 13.…”
Section: Zonal-flow Evolution Equationsmentioning
confidence: 99%
See 4 more Smart Citations
“…13 is connected only with the spectral analysis of investigation and we retain the main approach to the solving of the problem and all initial equations as in Ref. 13.…”
Section: Zonal-flow Evolution Equationsmentioning
confidence: 99%
“…Electronic mail: tamazគkaladze@yahoo.com was shown that the wave vector of the fastest growing zonalflow mode is perpendicular to that of the electrostatic drift pump wave. Thus the given paper may be considered as a generalization of the previous investigations and, for details, we refer the reader to Mikhailovskii et al 13 The paper is organized as follows: In Sec. II the spectral analysis of the problem is carried out and zonal-flow evolution equations in terms of electrostatic and vector potentials are obtained introducing the variables characterizing the zonal flows, the primary modes generating the flows, and the sideband amplitudes which depend on both the primary modes and zonal flows.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations